Pneumatization Patterns of the Petrous Apex and Lateral Sphenoid Recess - Malone, Alexander; Bruni, Margherita; Wong, Robert; Tabor, Mark; Boyev, K. Paul (Journal of Neurological Surgery Part B: Skull Base, 2017)
Introduction The petrous apex poses a challenge for surgical intervention due to poor access. As intraoperative image guidance and surgical instrumentation improve, newer endoscopic approaches are increasingly favored. This study aims to provide normative data on the anatomy of the lateral sphenoid sinus recess and petrous apex. These normative data could assist in determining the efficacy of a transnasal transsphenoidal approach to lesions of the anteroinferior petrous apex.Methods This is a retrospective study investigating normative data on all maxillofacial computed tomography (CT) scans performed at a level I trauma center over a 6-month period. All appropriate images had the pneumatization pattern of the petrous apex and lateral recess of the sphenoid sinus reviewed by a single otologist and graded bilaterally. These were then analyzed in SPSS; Pearson correlation analyses and χ2 test were used.Results A total of 481 patients were identified, yielding a total of 962 temporal bones and sphenoid sinuses for analysis. Eighty-eight percent of sides analyzed had a nonpneumatized lateral recess. The petrous apex was nonpneumatized in 54% of sides analyzed. There was a correlation noted between the degree of pneumatization of the petrous apex and pneumatization of the lateral recess of the sphenoid.Conclusion This study is the first to provide normative data comparing pneumatization of the petrous apex and sphenoid sinus. These data may support future work evaluating the utility of an endonasal approach to the petrous apex.
Keywords: petrous apex; sphenoid sinus; skull base; pneumatization